An unsuspected ameloblastoma in the subpontic region of the mandible with consideration of pathogenesis from the radiographic course - Siar, C.H.; Nakano, K.; Chelvanayagam, P.I.; Ng, K.H.; Nagatsuka, H.; Kawakami, T. (2010)
The purpose of this report is to document a case of unsuspected ameloblastoma involving the right mandibular subpontic region in a 38-year-old Cambodian female patient. This lesion was purportedly preceded by multiple radiolucencies which were diagnosed as radicular cysts and treated a few times in the past years by enucleation followed by endodontic therapy of the affected teeth. Bridgework restoration of the partially edentulous area was performed. This case report demonstrates radiographic changes that occurred in the periods before and after the diagnosis of ameloblastoma. The case may represent an example of radicular cysts and ameloblastoma occurring as a collision phenomenon, or the ameloblastoma may have arisen as a result of neoplastic transformation of the lining epithelium in an inflammatory odontogenic epithelial cyst.